Rancang Bangun Aplikasi Inventori dan Pendataan Penjualan Berbasis Android di PT. Kobam Pustaka Sejarah - Andy Dwi Prasetyo; Luthfi Nurhaikal; Fahmi Perdana; Muhamad Kevin Attarshah; Aries Saifudin (Journal of Research and Publication Innovation, 2023)
This study aims to address the issues of efficiency and speed in inventory management at PT. Kobam Pustaka Sejarah by developing a digital data processing application based on the Android platform. Utilizing the Android operating system, Flutter and Java programming languages, and Firebase database, this application simplifies the recording of incoming and outgoing goods as well as stock data in a more efficient manner. The research findings indicate that the implementation of this application successfully enhances the effectiveness of inventory management, expedites decision-making processes related to inventory, and improves customer satisfaction through faster and more accurate service. With the existence of this application, PT. Kobam Pustaka Sejarah can optimize resource utilization and reduce human errors in recording and monitoring inventory, consequently bringing positive impacts to the overall performance of the company